Prevalence of postpartum depression and associated risk factors in tertiary health care centre - Kiruba Nandini, M. Sri; Bhaskaran, Shanta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Postpartum depression (PPD) is defined as a depressive episode occurring during pregnancy or until 4-weeks post-childbirth. It is essential to diagnose postpartum depression since it can disrupt normal maternal and infant bonding and have a negative impact on both the short and long-term development of children. To determine the prevalence of postpartum depression and the associated risk factors in women delivering in a tertiary health care centre. Methods: A prospective observational study was conducted in a tertiary health care centre from January 2021 to June 2022 for a period of 18 months. Pregnant women were assessed using the Edinburgh postnatal depression scale (EPDS) at 2-3 days postpartum and at 6 weeks postpartum. The cut-off score for detecting major depression is a score greater than or equal to 13. Results: The study included 204 women, of which postpartum depression was present in 28 women. The prevalence of postpartum depression in this study group is 13.7%. Unplanned pregnancy, neonatal intensive care unit (NICU) admission of newborns, preterm delivery, lack of support from family, complications during pregnancy or birth, and delayed breastfeeding were significantly associated with postpartum depression. Conclusions: Psychological and emotional well-being should also be given priority in addition to the physical well-being of women. All women who are at high risk should be screened so that PPD can be detected earlier, and support should be extended in the form of counselling and treatment.